MODERN CONCEPTS AND CLINICAL EFFICACY OF LASER TECHNOLOGIES IN THE MANAGEMENT OF HEMORRHOIDAL DISEASE - Sadikov, Rasul; Sadikov, Rustam; Bobokulov, Khakim (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The aim of the study was to analyze current literature data on the use of laser technologies in the treatment of hemorrhoidal disease and to assess their clinical and pathogenetic significance in modern coloproctology.